MALDI Orbitrap Mass Spectrometry Profiling of Dysregulated Sulfoglycosphingolipids in Renal Cell Carcinoma Tissues - Jirásko, Robert; Holčapek, Michal; Khalikova, Maria; Vrána, David; Študent, Vladimír; Prouzová, Zuzana; Melichar, Bohuslav (Journal of the American Society for Mass Spectrometry, 2017)
Matrix-assisted laser desorption/ionization coupled with Orbitrap mass spectrometry (MALDI-Orbitrap-MS) is used for the clinical study of patients with renal cell carcinoma (RCC), as the most common type of kidney cancer. Significant changes in sulfoglycosphingolipid abundances between tumor and autologous normal kidney tissues are observed. First, sulfoglycosphingolipid species in studied RCC samples are identified using high mass accuracy full scan and tandem mass spectra. Subsequently, optimization, method validation, and statistical evaluation of MALDI-MS data for 158 tissues of 80 patients are discussed. More than 120 sulfoglycosphingolipids containing one to five hexosyl units are identified in human RCC samples based on the systematic study of their fragmentation behavior. Many of them are recorded here for the first time. Multivariate data analysis (MDA) methods, i.e., unsupervised principal component analysis (PCA) and supervised orthogonal partial least square discriminant analysis (OPLS-DA), are used for the visualization of differences between normal and tumor samples to reveal the most up- and downregulated lipids in tumor tissues. Obtained results are closely correlated with MALDI mass spectrometry imaging (MSI) and histologic staining. Important steps of the present MALDI-Orbitrap-MS approach are also discussed, such as the selection of best matrix, correct normalization, validation for semiquantitative study, and problems with possible isobaric interferences on closed masses in full scan mass spectra. Graphical Abstract ᅟ.
Keywords: ledviny; analýza hlavních komponent; Biomarkers, Tumor; Renal cell carcinoma; Carcinoma, Renal Cell; lidé; Orbitrap mass spectrometry; nádorové biomarkery; Kidney Neoplasms; Kidney; karcinom z renálních buněk; senzitivita a specificita; Sulfatide; sulfoglykosfingolipidy; Sensitivity and Specificity; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Multivariate Analysis; multivariační analýza; Humans; Principal Component Analysis; nádory ledvin; Sulfoglycosphingolipids; metoda nejmenších čtverců; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Least-Squares Analysis; MALDI